How Can Language Curriculum Theory Be Coherent with Practice Through Task-Based Learning in a Third Grader's EFL Classroom? (2018)
ABSTRACT: This paper presents an action research aimed at exploring the effectiveness of Task-Based Learning (TBL) for the language curriculum theory to be coherent with practice in an EFL third grader's classroom at the I.E Francisco Miranda in Medellín, Colombia. The data were collected through a journal, an interview to the cooperating teacher, a survey to the students, and two tasks done by the students. The data analysis revealed that TBL is an effective approach to get coherence between the institution's language curriculum objectives and classroom practices since it encourages the development of the communicative competences promoted by the English syllabus, whose main objective is communication. This research provides valuable information about the usefulness of TBL approach in communicative syllabi.